2011
DOI: 10.3238/arztebl.2011.0663
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials

Abstract: RCTs cannot yield reliable data unless they are planned, conducted, analyzed, and reported in ways that are methodologically sound and appropriate to the question being asked. The quality of any RCT must be critically evaluated before its relevance to patient care can be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 15 publications
0
49
0
4
Order By: Relevance
“…Još je Sir William Osler, jedan od osnivača moderne medicine, prije dva stoljeća izjavio: "Medicina je umjetnost temeljena na znanosti." 1 Glavna zadaća EBM-a jest ispitati djelotvornost svakog novog i postojećeg lijeka, terapijskog postupka ili kirurškog zahvata, te na temelju rezultata istraživanja odluči-ti koji je od njih adekvatan za pacijente 2 . Kamen temeljac EBM-a danas su randomizirana klinička istraživanja (engl.…”
Section: Uvodunclassified
“…Još je Sir William Osler, jedan od osnivača moderne medicine, prije dva stoljeća izjavio: "Medicina je umjetnost temeljena na znanosti." 1 Glavna zadaća EBM-a jest ispitati djelotvornost svakog novog i postojećeg lijeka, terapijskog postupka ili kirurškog zahvata, te na temelju rezultata istraživanja odluči-ti koji je od njih adekvatan za pacijente 2 . Kamen temeljac EBM-a danas su randomizirana klinička istraživanja (engl.…”
Section: Uvodunclassified
“…Comparisons of study results from trials with historical controls and trials with a randomised design revealed that in studies with historical controls the results were biased through trends in a single direction, which could be avoided by randomisation [8], [9]. RCTs are currently considered the gold standard of study designs [10]. Only meta-analyses and/or systematic review articles that analyse several RCTs and summarise them by using exactly defined methods with a specific question have an even higher value according to the OCEBM – evidence level Ia (2009 version) and evidence level 1 (2011 classification).…”
Section: Evidence-based Medicinementioning
confidence: 99%
“…Despite the above-mentioned limitations, randomised controlled trials are still considered the gold standard for confirming the efficacy of new therapeutic procedures [10]. They have the lowest risk for systematic bias [10], [22] and when correctly designed, they control best for placebo effects [22].…”
Section: Evidence-based Medicinementioning
confidence: 99%
“…Sicherlich sind kontrollierte randomisierte klinische Studien die goldene Basis für die Evidenz unserer klinischen Anwendungen [5]. Allerdings muss die Generalisierbarkeit, also die Übertrag-barkeit der Studienergebnisse auf die breite Patientenversorgung (externe Validität) oft in Frage gestellt werden, weil standardisierte und kontrollierte Studienbedingungen nur unzureichend die klinische Versorgungsrealität wiedergeben [2]. So gesehen, kann man aus klinischer Sicht auch von künstlichen Bedingungen in selektionierten Kollektiven spre- chen [5].…”
Section: Kommentarunclassified